Bone management in Japanese patients with prostate cancer: hormonal therapy leads to an increase in the FRAX score. Issue 1 (December 2016) - Kawahara, Takashi; Fusayasu, Shusei; Izumi, Koji; Yokomizo, Yumiko; Ito, Hiroki; Ito, Yusuke; Kurita, Kayo; Furuya, Kazuhiro; Hasumi, Hisashi; Hayashi, Narihiko; Myoshi, Yasuhide; Miyamoto, Hiroshi; et al.
Abstract Background Osteoporosis is a common consequence of androgen deprivation therapy (ADT) for prostate cancer. Up to 20 % of men on ADT have suffered from fractures within 5 years. The WHO Fracture Risk Assessment Tool (FRAX) has been utilized to predict the 10-year probability of major osteoporotic and hip fracture. However, to date, no large studies assessing the utility of the FRAX score in prostate cancer patients with or without ADT have been performed. We herein evaluated the impact of ADT on the FRAX score in prostate cancer patients. Methods The assessment of the FRAX score was performed in a total of 1220 prostate cancer patients, including patients who underwent brachytherapy (n  = 547), radical prostatectomy (n  = 200), external beam radiation therapy (n  = 264) and hormonal therapy alone (n  = 187) at Yokohama City University Hospital (Yokohama, Japan). We evaluated the effect of ADT on the FRAX score. Results Using the FRAX model, the median and mean 10-year probability of a major osteoporotic fracture according to the clinical risk factors alone was 7.9 % (8.8 ± 4.3 %), while the 10-year probability of hip fracture risk was 2.7 % (3.5 ± 3.1 %). In the ADT group, the duration of ADT was correlated with both major osteoporotic risk and hip fracture risk (R2  = 0.141, p  < 0.001 and R2  = 0.166, p  < 0.001, respectively). A comparison between the ADT (n  = 187) and non-ADT (n  = 399) groups demonstrated that the major fracture risk was > 20 % higher and the hip fracture risk was > 3 % higher in the ADT group than in the non-ADT group (ADT: 10 (5.3 %) and 118 (63.1 %), non-ADT 13 (3.3 %) and 189 (47.4 %), p  < 0.001 andp  < 0.001, respectively). Conclusions These results suggested that the longer duration of ADT led to an increased FRAX score, and the FRAX score may be a predictor of bone management treatment, particularly in prostate cancer patients.